Strategies for increasing students' participation in oral activities - a case of Dong Do High school, Hanoi - Nguyễn, Thùy Dương (ĐHNN, 2017)
Chapter one, Literature Review, presents various concepts most relevant to the research topic such as definition of strategies, teaching strategies; concepts of communicative language teaching (CLT); nature of speaking skill and principles of teaching speaking. Furthermore, the following are also included in this chapter: definition of students' participation, and factors affecting students' participation as well. Chapter two, namely “The Study” describes the overall picture of the research was carried out from the first step of determining the research design to the last step of gathering the results. Moreover, presentation of statistical results are describes in this chapter. Chapter three, “Statistics and Analysis of data” analyses the collected data to answer the three research questions. Chapter four, namely “Findings and Recommendations” presents the findings with conclusion and comment after the experiment was finished and suggests what teachers of English at DDHS should do to enlarge the students' participation in speaking activities.